The Effect of Mordan Alum, Betel Lime and Tunjung on The Ecoprint Results of Bitter Melons on Armani Silk Fabric - Sari, Febri Anita; Adriani, Adriani (Gorga : Jurnal Seni Rupa, 2025)
This research is motivated by the use of bitter melon leaves as an ecoprint motif using the ecoprint technique assisted by mordants and fixatives. The purpose of this study is to see the name of the color, the clarity of the shape of the motif, and the resistance of color fade to washing with alum mordants, betel lime, and tunjung. This research is an experimental research with the object of research - namely, Armani silk material produced by bitter melon leaf ecoprint using alum mordant, betel lime, and tunjung. The type of data is in the form of primary data with a data collection technique using filling in an instrument in the form of a questionnaire. Data analysis techniques with Friedman K-Related test using SPSS (Statistical Product and Service Solutions) version 29.0 program. The result of the ecoprint color name uses bitter melon leaves on Armani silk material with alum mordant producing olive color, betel lime mordant producing camouflage green color, and tunjung producing dark olive green color. The result of the clarity of the shape of the leaf motif on the mordant of alum, betel lime, and tunjung produces a clear clarity of the shape of the motif, which means that the shape of the leaf (leaf flesh, base of the leaf, and edge of the leaf) is clear on the material of Armani silk. The color fading resistance to washing as a result of applying bitter melon leaf ecoprint motifs on Armani silk materials using alum mordant, betel lime, and tunjung in washing the three colors was slightly reduced.